Joint profiling of histone modifications and transcriptome in single cells from mouse brain - Zhu, Chenxu; Zhang, Yanxiao; Li, Yang Eric; Lucero, Jacinta; Behrens, M. Margarita; Ren, Bing (Nature methods, 2021)
Genome-wide profiling of histone modifications can reveal not only the location and activity state of regulatory elements, but also the regulatory mechanisms involved in cell-type-specific gene expression during development and disease pathology. Conventional assays to profile histone modifications in bulk tissues lack single-cell resolution. Here we describe an ultra-high-throughput method, Paired-Tag, for joint profiling of histone modifications and transcriptome in single cells to produce cell-type-resolved maps of chromatin state and transcriptome in complex tissues. We used this method to profile five histone modifications jointly with transcriptome in the adult mouse frontal cortex and hippocampus. Integrative analysis of the resulting maps identified distinct groups of genes subject to divergent epigenetic regulatory mechanisms. Our single-cell multiomics approach enables comprehensive analysis of chromatin state and gene regulation in complex tissues and characterization of gene regulatory programs in the constituent cell types. Paired-Tag offers a multiomics assay for joint profiling of histone modifications and gene expression in single nuclei, and is applied to mouse frontal cortex and hippocampus for measuring cell-type-resolved chromatin state and transcriptome.